Optimized preference of security staff scheduling using integer linear programming approach - Ang, Shin Yin; Mohd Razali, Siti Noor Asyikin; Kek, Sie Long (COMPUSOFT, 2019)
This paper proposes an optimized schedule for security staff using integer linear programming approach. It is important to improve the life quality of the security staff since the negative social life such as family problems, less social support or even stress following from a poor work schedule. Therefore, this study aims to maximize the preference satisfaction of the security staff by allowing them to choose their preferred shift and day off while taking into consideration the restrictions of the university rules. The mathematical model of integer linear programming approach is developed and solved by using LPSolve IDE package. The result shows the overall preference satisfaction of the security staff towards work shift and days off is successfully maximized from 228.33 to 394.33. The comparison of the real schedule and the new proposed optimized schedule is made and all the constraints are successfully satisfied. The proposed schedule able to assist the university management in producing the most flexible and beneficial schedule for their staff to increase the satisfaction towards the working life.